Supporting statistics in the workplace: experiences with two hospitals. Issue 2 (2003) - Mortlock, M. Y.; Spencer, N.; Mengersen, K.
Abstract : This paper provides some reflections on the promotion of lifelong learning in statistics in the workplace. The initiative from which the reflections are drawn is a collaboration between a university and two public hospitals, of which one of the stated aims is to develop statistical skills among the hospitals' researchers. This is realized in the provision of 'biostatistical clinics' in which workplace teaching and learning of statistics takes place in one-on-one or small group situations. The central issue that is identified is the need to accommodate diversity: in backgrounds, motivations and learning needs of workplace learners (in this case medical researchers), in the workplace environments themselves and in the projects encountered. Operational issues for the statistician in providing such training are addressed. These considerations may reflect the experiences of the wider community of statisticians involved in service provision within a larger organization.